Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0132024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 60 Hz Magnetic Field Exposure Up to 3000 μT on Human Brain Activation as Measured by Functional Magnetic Resonance Imaging

Abstract: Several aspects of the human nervous system and associated motor and cognitive processes have been reported to be modulated by extremely low-frequency (ELF, < 300 Hz) time-varying Magnetic Fields (MF). Due do their worldwide prevalence; power-line frequencies (60 Hz in North America) are of particular interest. Despite intense research efforts over the last few decades, the potential effects of 60 Hz MF still need to be elucidated, and the underlying mechanisms to be understood. In this study, we have used fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 71 publications
(86 reference statements)
4
17
0
Order By: Relevance
“…Interestingly, EEG data provide a consistent view with BOLD (acquired simultaneously) results, suggesting an absence of EEG effects due to 3 mT 60 Hz MF exposure on brain electrical or functional activity. It is worth mentioning that the level of MF flux density during this sequence was identical to previous research in our group [Legros et al, ], while the exposure duration was different (60 min in previous research, 10 s repeated 12 times in the present study). In terms of accumulated time of exposure, it sums up to 2 min for the current study versus 60 min in previous research where significant effects on brain functional activation were identified [Legros et al, ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, EEG data provide a consistent view with BOLD (acquired simultaneously) results, suggesting an absence of EEG effects due to 3 mT 60 Hz MF exposure on brain electrical or functional activity. It is worth mentioning that the level of MF flux density during this sequence was identical to previous research in our group [Legros et al, ], while the exposure duration was different (60 min in previous research, 10 s repeated 12 times in the present study). In terms of accumulated time of exposure, it sums up to 2 min for the current study versus 60 min in previous research where significant effects on brain functional activation were identified [Legros et al, ].…”
Section: Discussionsupporting
confidence: 87%
“…It is worth mentioning that the level of MF flux density during this sequence was identical to previous research in our group [Legros et al, ], while the exposure duration was different (60 min in previous research, 10 s repeated 12 times in the present study). In terms of accumulated time of exposure, it sums up to 2 min for the current study versus 60 min in previous research where significant effects on brain functional activation were identified [Legros et al, ]. Therefore, participants to the present study have been exposed for a duration 30 times lower, with an identical MF flux density, suggesting that MF exposure duration might be a critical parameter in possible neurophysiological effects.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Various types of human cells derived from iPS cells could be utilized for assessment of the health risks of various targets, including EMFs. The current international guidelines/standards for low-frequency EMF exposure deserve further investigation on many points, and experimental data on human neural responsiveness to EMFs have attracted much interest in recent years (Legros et al, 2012(Legros et al, , 2015. We propose that data on muscles, in particular CMs, should be similarly collected for evaluation of the risk of exposure to EMFs.…”
Section: Discussionmentioning
confidence: 99%